Clean Energy vis-à-vis Capital Extraction - Dhien Favian (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
This article examines the paradoxical aspects of the Arjuno-Welirang geothermal project in Batu City, which, due to its exploitative nature, has the potential to threaten the availability of springs. Theoretically, the study employs Social Conflict Theory (SCT) and a political economy approach to analyse how energy transition projects operate according to the logic of capital accumulation. Using a qualitative case study method involving field observations of residents' advocacy against the project in Batu City, as well as a literature review, the study finds that the Arjuno-Welirang project is deeply entrenched in the dynamics of an infrastructure alliance (comprising the state, financial institutions and corporations), which functions as a specific manifestation of a dominant social alliance. This alliance strategically utilises the narrative of a green energy transition to facilitate an extractive project that endangers the material foundation of local communities. In response, the mobilisation of Batu residents constitutes anticipatory grassroots resistance organised as a material struggle to defend their ecological commons and water resources from the monopolistic threats posed by energy capitalism.